An Overview of the Results and Widespread Effects of the Hazelnut Gardens Rehabilitation Project in Ordu Province and Region - Tugce DENIZ; Gurdil, Gurkan A. K.; Hidayat, Benny; DEMIREL, Bahadir (Jurnal Online Pertanian Tropik, 2024)
This paper provides a comprehensive overview of the results and widespread effects of the Hazelnut Gardens Rehabilitation Project in Ordu Province and the surrounding region of northeastern Türkiye. The project launched some years ago, aimed to revitalize the region's vital hazelnut industry by addressing challenges such as aging hazelnut orchards, poor agricultural practices, and environmental degradation. The paper examines the multifaceted impacts of the rehabilitation efforts through quantitative data analysis and qualitative interviews with stakeholders. Key outcomes include significant hazelnut yields and quality increases, improved soil health and water conservation, and enhanced economic opportunities for local farmers and businesses. Additionally, the study explores the ripple effects on the region's environmental sustainability, food security, and social fabric. By empowering smallholder farmers, promoting organic cultivation, and fostering community engagement, the project has catalyzed a broader transformation in the way the hazelnut industry operates in Ordu. The findings offer valuable insights for policymakers, agricultural development practitioners, and other stakeholders seeking to replicate or scale up similar initiatives to revitalize traditional crop systems and enhance rural livelihoods. The paper concludes with recommendations for sustaining the project's momentum and maximizing its long-term benefits for the Ordu region and beyond.